(untitled) (Costos y Gestión, 2024)
Sustainability is a topic currently being discussed of great importance, in which analysis can be carried out on corporate business models based on their value chain. Cuba, which as a state is not immune to these issues, is immersed in changing its energy matrix through the use of renewable energy, to reduce the consumption of imported fossil fuels to generate electricity. The objective of the work is to diagnose sustainability in the environmental, economic and social dimensions through the use of the value chain of photovoltaic panels in the Electronic Components company, Pinar del Río, Cuba. The methodology used is qualitative, to validate the diagnosis of the sustainability of the value chain of photovoltaic panels in Cuba, the Delphi method is applied using expert criteria. The results are related to the validation of each of the proposed indicators in the three dimensions, for their subsequent ap- plication in the value chain under study.